(3GdCefjGJ aj eYQaI GdMejGJs
(3ChdgG (B:s
(3GdMeO ddg GdYdje aEf MGOK GdMei MGOK NWjQ, hMed GdfahS dCZQGVgG UYH YSjQ, dCfgG JgOe CQcGf GdCLSGe ajaSO fXGegG s
(3BNQgG (B:s
(3hGdCeQGV GdJj jcKQ ajgG GdfcS GdUOGY hGdQeO hVjb GdfaS, hGdMUHI EPG de jcf bO JcGed NQhLgG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B31 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B(71) ((3WH (B7394) s
Keywords: (3GdWHs